ENHANCING THE CONTRIBUTION OF PREFERENTIAL TRADE AGREEMENTS TO INCLUSIVE AND EQUITABLE TRADE: THE CASE OF MONGOLIA - N.Batnasan (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
In recent years, the number of preferential trade agreements (PTAs) increases rapidly. These agreements have a range of advantages compared with the multilateral regime, and have become a popular tool for regional economic cooperation. Despite its popularity, however, many economists are still skeptical of the effectiveness of PTAs. This study will attempt to present a clear understanding about the economic and social impacts of such preferential trade agreements on Mongolian economy and society, and to draw some policy conclusions. Within this framework the current study, there are multiple objectives as follows: (1) to provide background information on trade and economic situation in Mongolia; (2) to throw light on economic growth, trade, poverty and employment nexus in the Mongolian context; and, (3) to analyze preferential trade agreements of Mongolia and their impact on the country’s economy.